Desempenho ocupacional da pessoa idosa frágil e a sobrecarga do cuidador - Roso, Bruna Flôres (2024)
Population aging is already a consensus in the literature. Along with this process, there are changes resulting from chronic non-communicable diseases (NCDs) that compromise the occupational performance of the elderly, becoming a predictor of frailty syndrome. Thus, the need for assistance from a caregiver arises during the performance of activities of daily living (ADLs) and instrumental activities of daily living (IADLs). Care provided at home is complex and can generate physical, psychological, and emotional overload and social isolation. Thus, there is a need for in-depth studies on the impacts that care can generate on the quality of life of informal caregivers, verifying the relationship between these, especially the overload, and the occupational performance of the elderly person. Therefore, the objective of this research is to analyze the relationship between the occupational performance of the frail elderly person and the overload of the caregiver. The research is characterized as observational, crosssectional and with a mixed approach – quantitative and qualitative. Data collection was carried out with elderly individuals treated at the Occupational Therapy Outpatient Clinic of the Santa Maria University Hospital, and the informal caregivers who accompanied them, from August 2023 to April 2024. Elderly individuals who were not accompanied by their caregivers or for whom it was not possible to apply all the instruments, as well as formal caregivers, were excluded. For the collection with the elderly, the Mini Mental State Examination (MMSE), the Comprehensive Geriatric Assessment (CGA); the Frail Scale and the Canadian Occupational Performance Measure (COPM) were applied. For the collection with the caregivers, a questionnaire regarding sociodemographic data, health profile and aspects inherent to care and the Zarit Burden Scale were applied. The association between Frail and Zarit was analyzed by the Chi-Square test. The correlation between COPM and Zarit was analyzed by Pearson's correlation coefficient. p<0.05 was considered a significant difference. All analyses were performed using the Statistical Package for Social Science Windows - 26. Qualitative analysis was performed using Bardin's content analysis, through thematic categories. The final research sample consisted of 20 frail elderly individuals accompanied by their caregivers. Regarding the sociodemographic and health profile of the elderly, women predominated, with a mean age of 76.7 years, low education level, cardiovascular NCDs, occupational performance with a mean of 4.9 and satisfaction 5.1. Regarding caregivers, women predominated, spouses or children, with a mean age of 57.6 years, married marital status, cardiovascular NCDs and burden score 2.0. Among the changes and difficulties of care are family relationships, assistance during ADLs, the need to abandon work and the lack of rest/leisure moments. There was a correlation between the occupational performance of the elderly and the burden of the caregiver. The results of this research point to a possible relationship of security and trust between those who provide care and those who receive care, since as the elderly feel satisfied, caregivers feel less overwhelmed.